2010
DOI: 10.1007/s11999-009-1021-5
|View full text |Cite
|
Sign up to set email alerts
|

The Ischial Spine Sign: Does Pelvic Tilt and Rotation Matter?

Abstract: Although the ischial spine sign (ISS) has been advocated to detect acetabular retroversion, it is unknown whether the sign is valid on anteroposterior (AP) pelvic radiographs with tilted or rotated pelves. We therefore evaluated reliability of the ISS as a tool for diagnosing acetabular retroversion in the presence of considerable pelvic tilt and/or malrotation. We obtained radiographs of 20 cadaver pelves in 19 different malorientations resulting in 380 pelvis images (760 hips) for evaluation. In addition, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 11 publications
0
54
0
3
Order By: Relevance
“…We used standing films as the functional position and compared values from that position with values from the supine position. In another study [5], the ischial spine was found to be more prominent with forward tilt. Through these studies, it has been shown that increased forward tilt of the pelvis results in more-prominent crossover and ischial spine signs, both signs of acetabular retroversion and a cause for pincer impingement.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…We used standing films as the functional position and compared values from that position with values from the supine position. In another study [5], the ischial spine was found to be more prominent with forward tilt. Through these studies, it has been shown that increased forward tilt of the pelvis results in more-prominent crossover and ischial spine signs, both signs of acetabular retroversion and a cause for pincer impingement.…”
Section: Discussionmentioning
confidence: 83%
“…Although 46 hips were used for analysis, the inclusion of more hips can allow for more accurate analysis and detect trends and correlations. The reason for a small cohort was attributable to strict exclusion criteria, mainly malrotated films, which can have an effect on the presence or absence of a crossover sign [5]. The limitation of the quality of radiographs is important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of surgical hip dislocations with rim trimming reached the maximum between 2004 and 2008. During this time, we learned that acetabular retroversion (defined as having all three signs) is a result of rotation of the hemipelvis [8,15,16,44,49]. In addition, the size of the lunate surface and the outer margin of the acetabular rim are normal in retroversion [44] and can theoretically be reduced in a critical way by rim trimming [3].…”
Section: Methodsmentioning
confidence: 99%
“…Acetabular retroversion was initially understood as a prominent overgrowth of the anterior acetabular wall [4], but there is increasing evidence that acetabular retroversion is a rotational abnormality of the entire hemipelvis [15,16,28,36,44,49] rather than focal overgrowth.…”
Section: Introductionmentioning
confidence: 99%